Mosaicism in neurofibromatosis type 2: an update of risk based on uni/bilaterality of vestibular schwannoma at presentation and sensitive mutation analysis including multiple ligation-dependent probe amplification. Issue 7 (16th February 2007) - Evans, D Gareth R; Ramsden, R T; Shenton, A; Gokhale, C; Bowers, N L; Huson, S M; Pichert, G; Wallace, A
Abstract : Background: Neurofibromatosis type 2 (NF2) is almost unique among inherited disorders in the frequency of mosaicism in the first affected generation. However, the implications of this on transmission risks have not been fully elucidated. Methods: The expanded database of 460 families with NF2 and 704 affected individuals was analysed for mosaicism and transmission risks to offspring. Results: 64 mosaic patients, with a projected mosaicism rate of 33% for sporadic classical NF2 with bilateral vestibular schwannoma at presentation and 60% for those presenting unilaterally, were identified. Offspring risks can be radically reduced on the basis of a sensitive mutation analysis of blood DNA including multiple ligation-dependent probe amplification (MLPA, which detects 15% of all mutations), but even MLPA cannot detect high levels of mosaicism. Conclusion: The chances of mosaicism in NF2 and the resultant risks of transmission of the mutation to offspring in a number of different clinical situations have been further delineated. The use of MLPA in this large NF2 series is also reported for the first time.